Intellectual property as a factor of effective business - Gliznutsa, M. Yu.; Pererva, P. G. (ТОВ "Юридична компанія "Юрсервіс", 2023)
Among the main negative processes taking place in the field of entrepreneurship, it can be noted a decrease in the productivity of employees, an increase in staff turnover, a decrease in the level of qualification of personnel and the associated weakening of the intellectual potential of the enterprise, and therefore, a slowdown in the pace of development of business and entrepreneurship.
Інтелектуальна власність як фактор ефективного бізнесу
Keywords: intellectual property; business activity; economic efficiency; enterprises